Tax Professionals' Role and Ethics During A Period of Economic Crisis in A Small European Country - Michail Pazarskis; Athanasia Karakitsiou; Andreas Koutoupis; Despoina Sidiropoulou (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: This paper analyses the role and ethics of tax professionals in the collection of public revenue from business activity during a period of economic crisis in Greece. Motivation - We attempt to analyse the respective influences of a corporate environment and personal beliefs on tax professionals' ethics as well as the consequences of economic crisis. Idea: The paper employs a modified experimental questionnaire from Bobek & Radtke (2007) for the US. This questionnaire is adapted for Greece during a period of economic crisis. Data - Addressees of the questionnaire were tax professionals of two categories: certified public accountants and accountant/tax consultants, both of which are responsible for determining the amount of taxes owed to the Greek Independent Public Revenue Authority (IPRA). Tools - Results were reached by submitting the results of a questionnaire to a multiple-correspondence analysis based on the Burt matrix. As the size of the sample is rather small, in order to avoid any bias the study employs a resampling procedure based on the k fold validation method. Findings - The results of the survey showed that the main causes of ethical dilemmas are problems with clients such as pressure from clients, client-retention concerns and misunderstandings with clients. The major factor contributing to the resolution of an ethical dilemma is the experience of the tax professional. A significant percentage of respondents believed that their level of morality had increased during the period of economic crisis, making them more compliant with relevant tax rules. Contribution - This study contributes to business ethics and helps reinforce them, thereby contributing to the increase in the public revenues, which can help a economy to emerge faster from an economic crisis. Also, we recommend the targeting on in-house ethics training and explicitly including rewards and sanctions regarding ethical behavior in performance evaluation systems in tax professionals' firms.
Keywords: H20; M40; 650; tax professionals; ethics; public revenues; tax compliance; Greece